Efisiensi Produksi Usahatani Padi Sawah Lebak di Kabupaten Ogan Ilir Sumatera Selatan - Rahmi Hidayati; Komala Sari (Seminar Nasional Lahan Suboptimal, 2018)
Hidayati et al, 2019. Efficiency of Rice Waste Rice Production Factors in Ogan Ilir District, South Sumatera. pp. 249-259.The Province of South Sumatra has produced rice from four typologies, namely: irrigated rice fields, rain fed, tidal and non-receding tidal swamps (lebak). The development of agriculture in swamps faces obstacles both in the biophysics of land and water, pre-harvest and post-harvest handling as well as socio-economic. However, it must be admitted that the development of tidal land and lebak land is increasingly important to support national rice production. The right allocation of production factors is an important factor in increasing rice production, including land, seeds, labor, fertilizers, and pesticides. Therefore, to increase farmers' production and income, it is necessary to study what factors influence the production of lebak paddy rice farming and evaluate the performance of farmers in rice cultivation so that the level of efficiency of the use of production facilities for rice production is obtained in the field of lebak rice, especially in Ogan Regency Ilir. The research method used is a simple random sampling method. The data used are primary data and secondary data. The results of this study: There are four explanatory variables that significantly influence the production of lebak rice, namely land, seeds, urea fertilizer, pesticide use. While the other three have no significant effect, namely Sp-36 (P) fertilizer, phonska fertilizer (NPK) and labor deployment. Production factors that have been efficient in their use in lebak paddy rice farming are seeds, urea fertilizer, NPK fertilizer and pesticides and labor while the SP-36 fertilizer is inefficient. The income analysis found that the average lebak rice production was 4,144.64 kg / ha / mt / year. Average income is Rp 15,977,539.42 per hectare.